"A Fit Companion for a Woman of Sense": Jane West's Re-Education of Masculine Norms in Letters Addressed to a Young Man (1802) and The Infidel Father (1802). Issue 2 (3rd April 2021) - Woodworth, Megan A.
ABSTRACT: Jane West's novel, The Infidel Father (1802), carefully undercuts traditional norms, including the usual focus of the didactic novel – making a woman a fit companion for a man of sense. Traditionally considered an anti-Jacobin novelist, Jane West's contributions to the social and political debates of the Revolutionary era are being reevaluated. Known primarily for her fiction, she also wrote conduct books – including one for young men – which, as a writer of fiction, gives additional clues to the stakes of her writing on men. Letters Addressed to a Young Man on his First Entering Society (1801) and The Infidel Father (1802) are a productive pairing for exploring West'srecalibration of contemporary British masculinity. These texts are in dialogue with earlier manuals of advice, especially Chesterfield's Letters in their rejection of duplicitous courtliness and a preference for honesty in both public and private matters. The novel presents everything that is wrong with masculinity in the figure of the Infidel Father and invests the hero with a masculinity that is less performative and more informed by genuine feeling and goodness. Read together, they show West's blueprint for a different kind of Englishman and, by extension, English family and English nation.